Tantangan dan Strategi dalam Berwirausaha Warung Bakso dan Mie Ayam pada Era Digital - Alvin Pratama (Jurnal Sosial Humaniora dan Pendidikan, 2024)
People who have high levels of creativity and innovation in their lives are synonymous with entrepreneurship. The forms of entrepreneurship in society are very diverse, especially culinary traders who start their own businesses. Entrepreneurship in the culinary sector has great opportunities and promising results for business actors, including meatball and chicken noodle stall businesses which are popular and are the favorite food of every group. Meatball stall businesses are mushrooming in various places, one of which is the Sri Rama meatball and chicken noodle shop on Jalan Perjuangan, Medan Perjuangan District. This research aims to analyze and identify the challenges and entrepreneurial strategies carried out by the owner of the Sri Rama meatball and chicken noodle stall. The research method used is a qualitative descriptive method through several data collection techniques, namely observation, interviews and literature review. Based on the research results, it was found that the Sri Rama Chicken Meatball and Noodle shop business is one of the most popular meatball stalls around Medan Perjuangan District. There are several obstacles faced, one of which is uncertain market conditions. Having survived until now reaching 5 years, the stall owner has implemented a number of strategies, such as maintaining the image of the meatball taste and innovating by creating new meatball variants that attract consumers.